2011
DOI: 10.1007/s12020-011-9467-0
|View full text |Cite
|
Sign up to set email alerts
|

Value of repeat ultrasound-guided fine-needle aspiration in thyroid nodule with a first benign cytologic result: Impact of ultrasound to predict malignancy

Abstract: This study aimed to investigate the value of repeat ultrasound-guided fine-needle aspiration (FNAC-US) in benign thyroid nodules and determine the ultrasound (US) predictors of malignancy in this group of nodules. The authors studied 35 of 143 nodules with initially benign cytological result who underwent serial re-biopsy (FNAC-US). By means of surgery, malignancy histology results were confirmed in 10 (28.5%) cases (G1) versus 25 (71.5%) benign nodules (G2). The clinical, lab, scintigraphyc, and US features w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 27 publications
2
6
0
Order By: Relevance
“…Interestingly, a very high cancer rate (32 %) was found. This finding was perfectly in agreement with that previous reported by papers analyzing the likelihood for malignancy in these specific nodules [46][47][48]. More recently, CNB or conventional FNAC was proposed to patients with newly discovered at risk thyroid lesions [24]; the diagnostic accuracy of CNB was significantly higher than that of FNAC [24].…”
Section: Use Of Cnb In Thyroid Neoplasms (Thy 3/class 3/category Iii-supporting
confidence: 91%
“…Interestingly, a very high cancer rate (32 %) was found. This finding was perfectly in agreement with that previous reported by papers analyzing the likelihood for malignancy in these specific nodules [46][47][48]. More recently, CNB or conventional FNAC was proposed to patients with newly discovered at risk thyroid lesions [24]; the diagnostic accuracy of CNB was significantly higher than that of FNAC [24].…”
Section: Use Of Cnb In Thyroid Neoplasms (Thy 3/class 3/category Iii-supporting
confidence: 91%
“…We confirmed that in both examined groups malignant lesions showed at least 2 malignancy risk features more often than benign lesions. It is concordant with observations by Gul et al 2010 that the presence of CT seems to have no effect on the US characteristics of malignant nodules [33] as well as the other observations indicating that it is rational to perform repeat FNA of ultrasonographically suspected lesions [12, 3436]. …”
Section: Discussionsupporting
confidence: 91%
“…Investigations into selecting repeat FNA as a management approach for thyroid nodules with benign cytology using US features have been done and reported on in a few institutions [13], [28], [34], [35]. Therefore, we investigated the management algorithm for thyroid nodules with benign cytology using US features from data collected from multiple institutions.…”
Section: Discussionmentioning
confidence: 99%